Development and characterization of edible film from ambueong (Metroxylon saga Rottb.) - Yeban, Abbie Rose J. (2013.)
Ambueong (Metroxylon saga Rottb.) is locally used to make ambueong suman and other snack foods in Aklan.
Thesis (Undergraduate. Bachelor of Science in Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Ambueong